The making of a dissenting economist: Amit Bhaduri (1940-) - Bhaduri, Amit (PSL Quarterly Review, 2019)
The paper surveys the author’s research from a personal and autobiographic perspective. The author highlights the political interest and motivations behind the study of economics, as well as discusses some political consequence of economic research. The article focuses on the authors’ contributions on growth, development, and the Indian economy and society. JEL codes: B31, E12, O11